PENGARUH PENGETAHUAN AUDIT, INDEPENDENSI DAN PENGALAMAN AUDITOR TERHADAP KUALITAS HASIL AUDIT INVESTIGASI PADA AUDITOR INSPEKTORAT JENDERAL KEMENTRIAN KEUANGAN - Imron, Muhammad Ali; Widyastuti, Tri; Amilin, - (E-Journal Widya Ekonomika, 2018)
In order to guarantee the quality of audit results, has been set Auditing Standards. This research aims to determine the influence of audit knowledge, independence and auditor's experience to quality of audit investigation. In this research, independent variables are audit knowledge, independence, and auditor's experience and the dependent variable is quality of audit investigation. The method used is a technique of analysis by method of Ordinary Least Squares with mutiple linier regression. This research uses primary data by using a questionnaire to collect auditor's perception of the variables tested. The samples taken are 130 auditors in Inspectorate General of the Ministry of Finance. The results of this study explains that: (1) Three independent variables have a significant influence on the dependent variable simultaneouslyÍ¾ (2) There is a significant influence on variables of audit knowledge toward quality of audit investigation partiallyÍ¾ (3) There is a significant influence on variables of auditor's independence toward quality of audit investigation partiallyÍ¾ (4) There is a significant influence on variables of auditor's experience toward quality of audit investigation partially.